2018
DOI: 10.1186/s13068-018-1053-8
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal analysis of pretreated biomass species highlights generic markers of lignocellulose recalcitrance

Abstract: BackgroundBiomass recalcitrance to enzymatic hydrolysis has been assigned to several structural and chemical factors. However, their relative importance remains challenging to evaluate. Three representative biomass species (wheat straw, poplar and miscanthus) were submitted to four standard pretreatments (dilute acid, hot water, ionic liquid and sodium chlorite) in order to generate a set of contrasted samples. A large array of techniques, including wet chemistry analysis, porosity measurements using NMR spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 67 publications
3
53
1
Order By: Relevance
“…So, the enzyme cocktail EM0925 was much more effective than the current commercial products under the conditions tested, since only 46.9% sugar yield was acquired from UGCS by Celluclast 1.5 L after 72 h hydrolysis [33] (Table S1). In general, saccharification efficiency of lignocellulose biomass by EM0925 was better than that in any other literature reported under the conditions tested [29][30][31][32][33][34]. To be specific, in our study, the maximum 85.59% glucose yield and 66.18% xylose yield were obtained from UGCS hydrolyzed with 30 FPU/g of Celluclast 1.5 L used; while 100% glucose yield and 100% xylose yield were obtained from UGCS and ALKCS with the same enzyme dosage of T. harzianum EM0925.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…So, the enzyme cocktail EM0925 was much more effective than the current commercial products under the conditions tested, since only 46.9% sugar yield was acquired from UGCS by Celluclast 1.5 L after 72 h hydrolysis [33] (Table S1). In general, saccharification efficiency of lignocellulose biomass by EM0925 was better than that in any other literature reported under the conditions tested [29][30][31][32][33][34]. To be specific, in our study, the maximum 85.59% glucose yield and 66.18% xylose yield were obtained from UGCS hydrolyzed with 30 FPU/g of Celluclast 1.5 L used; while 100% glucose yield and 100% xylose yield were obtained from UGCS and ALKCS with the same enzyme dosage of T. harzianum EM0925.…”
Section: Discussioncontrasting
confidence: 53%
“…Monosaccharides yield was 865.5 mg/g of UGCS and 1073 mg/g of ALKCS, which was 1.29 and 1.31-fold of the highest monosaccharide yield obtained by Celluclast 1.5 L. In addition, the highest sugar yield from UGCS was obtained when EM0925 was applied at the dosage corresponding to 1/6 of the Celluclast 1.5 L dose (Figure 6a,b). These saccharification yields are among the highest yields reported in literature [29][30][31][32][33][34] (Table S1).…”
Section: Discussionmentioning
confidence: 58%
“…Hemicelluloses act as a physical barrier limiting the accessibility of enzymes. It has been reported that removal of hemicelluloses by dilute acid or steam explosion pre-treatment could increase cellulose conversion by improving the accessibility of enzymes to cellulose (Auxenfans et al, 2017a;Herbaut et al, 2018;Santos et al, 2018). Kruyeniski et al (2019) reported that the removal of hemicelluloses on pre-treated pine improved the fibers porosity and the area available for enzymes.…”
Section: Hemicelluloses and Acetyl Groupsmentioning
confidence: 99%
“…Also, it can irreversibly adsorb cellulases and other enzymes during enzymatic hydrolysis due to its hydrophobic structural features including hydrogen bonding, methoxy groups, and polyaromatic structures (Kumar and Wyman, 2009b;Zeng et al, 2014). Previous studies showed that the lignin content was negatively correlated with enzymatic digestibility in poplar (Meng et al, 2017;Yoo et al, 2017a), also in miscanthus, in wheat straw (Herbaut et al, 2018) and in transgenic rice (Huang et al, 2017). The removal of lignin generally disrupts the lignincarbohydrates matrix, increases the porosity and reduces nonproductive adsorption sites for enzymes (Pihlajaniemi et al, 2016;Kruyeniski et al, 2019).…”
Section: Ligninmentioning
confidence: 99%
“…The interference by lignin and hemicelluloses, which are intimately associated with cellulose fibrils in the lignocellulosic matrix, is a major factor contributing to the biomass recalcitrance. Although lignin content has been considered to be one of the main obstacles for cellulose enzymatic hydrolysis, a recent report points towards a more crucial role of lignin composition, in particular the content of syringyl and guaiacyl units and the amount of aryl ether linkages, as a key impediment for access of enzymes to the polysaccharides [18]. The capacity of lignin and pseudo-lignin, a product of carbohydrate degradation during thermal processing, to non-productively bind cellulases is another factor contributing to biomass recalcitrance [19].…”
Section: Lignocellulosic Feedstocksmentioning
confidence: 99%